Asymmetry of the pelvic ring evaluated by CT‐based 3D statistical modeling. Issue 5 (31st December 2020) - Handrich, Kristin; Kamer, Lukas; Mayo, Keith; Sawaguchi, Takeshi; Noser, Hansrudi; Arand, Charlotte; Wagner, Daniel; Rommens, Pol M.
Abstract: The human pelvis is a complex anatomical structure that consists of the innominate bones, sacrum and coccyx to form the pelvic ring. Even though considered to be a symmetric entity, asymmetry of the pelvic ring (APR) might occur to alter its anatomy, function, or biomechanics or to impact assessment and treatment of clinical cases. APR and its assessment is complicated by the intricate anatomy of the pelvic ring. There is only limited information and understanding about APR with no established evaluation methods existing. The objective of the present study was to adopt CT‐based 3D statistical modeling and analysis to assess APR within the complex anatomy of the pelvic ring. We were interested to establish a better understanding of APR with knowledge and applications transferred to human anatomy, related research, and development subjects and to clinical settings. A series of 150 routine, clinical, pelvic CT protocols of European and Asian males and females (64 ± 15 (20–90) years old) were post‐processed to compute gender‐ and ancestry‐specific 3D statistical models of the pelvic ring. Evaluations comprised principal component analysis (PCA) that included size, shape, and asymmetry patterns and their variations to be assessed. Four different CT‐based 3D statistical models of the entire pelvic ring were computed according to the gender and ancestry specific groups. PCA mainly displayed size and shape variations. Examination of additional PCA modes permitted six distinct asymmetry patterns to be identified. They were located at the sacrum, iliac crest, pelvic brim, pubic symphysis, inferior pubic ramus, and near to the acetabulum. Accordingly, the pelvic ring demonstrated not to be entirely symmetric. Assessment of its asymmetry proved to be a challenging task. Using CT‐based 3D statistical modeling and PCA, we identified six distinct APRs that were located at different anatomical regions. These regions are more prone to APRs than other sites. Minor asymmetry patterns have to be distinguished from the distinct APRs. Side differences with regard to size, shape, and/or position require to be taken into account. APRs may be due different load mechanisms applied via spine or lower extremity or locally. There is a need for simpler and efficient, yet reliable methods to be routinely transferred to human anatomy, related research, and development subjects and to clinical settings. Abstract : Using CT‐based 3D statistical modeling and principal component analysis we were able to identify six distinct regions of the pelvic ring, which can exhibit asymmetries. PC 7 of the European females is an example showing all of the six asymmetries of the pelvic ring located at the sacrum, the iliac crest, the pelvic brim, the acetabulum, the pubic symphysis and the inferior pubic ramus.